Ancient tales of giants from Qumran and Turfan: contexts, traditions, and influences - Goff, Matthew J.; Stuckenbruck, Loren T.; Morano, Enrico (Wissenschaftliche Untersuchungen zum Neuen Testament, 2016)
Cover -- Preface -- Table of Contents -- Matthew Goff: Introduction -- Part One: Gibborim and Gigantes. Antecedents, Reception, and Comparative Contextsfrom the Hebrew Bible and Greek Literature -- Brian R. Doak: The Giant in a Thousand Years: Tracing Narratives of Gigantism in the Hebrew Bible and Beyond -- I. The Embarrassing and Alluring Giant -- II. Five Categories of Giant Thinking in the Hebrew Bible -- 1. The giant as divine or semi-divine figure -- 2. The giant as anti-law and anti-king -- 3. The giant as elite adversary and elite animal